Failure of Miltefosine Treatment in Two Dogs with Natural Leishmania infantum Infection. (14th August 2014) - Proverbio, Daniela; Spada, Eva; Bagnagatti De Giorgi, Giada; Perego, Roberta
Abstract : Two dogs, with naturally acquired canine leishmaniasis, were treated orally with miltefosine (2 mg/kg q 24 hr) and allopurinol (10 mg/kg q 12 hr) for 28 days. Both dogs showed good initial response to therapy, with reduction in clinical signs and improvement of clinicopathological changes. However, in both dogs, clinical and clinicopathological abnormalities recurred 150 days after initial treatment and a second course of miltefosine and allopurinol was administered. One dog failed to respond to the 2nd cycle of miltefosine treatment and the other dog responded initially but suffered an early relapse. Treatment with meglumine antimoniate (100 mg/kg q 24 hr for a minimum of 4 weeks) was then started in both dogs. Both dogs showed rapid clinical and clinicopathological improvement and to date they have not received further treatment for 420 and 270 days, respectively. In view of the low number of antileishmanial drugs available and the fact that some of these are used in human as well as veterinary medicine, it is of paramount importance that drug resistance is monitored and documented.